2011
DOI: 10.1590/s1806-66902011000200010
|View full text |Cite
|
Sign up to set email alerts
|

Influência da irrigação com água salina na cultura do girassol

Abstract: Resumo -O presente experimento foi realizado com o objetivo de avaliar a influência da irrigação com água salina no crescimento e na produção de girassol (híbrido H251), além de monitorar a evolução de alguns atributos químicos do solo ao longo do ciclo da cultura. O delineamento experimental foi em blocos casualizados com seis tratamentos e cinco repetições. Os tratamentos consistiram de seis diferentes estratégias de irrigação, sendo cinco delas com utilização de água salina. As avaliações de crescimento (al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 16 publications
2
12
1
12
Order By: Relevance
“…This is due to the increment of salinity in the water or in the soil, with negative reflexes in the vegetative and productive behaviour of the crop (GUEDES FILHO et al, 2015). The results of present study differ from those observed by Morais et al (2011), who concluded that increasing salinity in the irrigation water of up to 3.5 dS m -1 did not compromise sunflower productivity (Hybrid H251). These different responses to salinity may vary between cultivars of a same species, with phenological stage, strategy of water application and exposure time to the salts (SAVVAS et al, 2007).…”
Section: Figure 2 Number Of Viable Achenes In Sunflower CV "Embrapacontrasting
confidence: 99%
“…This is due to the increment of salinity in the water or in the soil, with negative reflexes in the vegetative and productive behaviour of the crop (GUEDES FILHO et al, 2015). The results of present study differ from those observed by Morais et al (2011), who concluded that increasing salinity in the irrigation water of up to 3.5 dS m -1 did not compromise sunflower productivity (Hybrid H251). These different responses to salinity may vary between cultivars of a same species, with phenological stage, strategy of water application and exposure time to the salts (SAVVAS et al, 2007).…”
Section: Figure 2 Number Of Viable Achenes In Sunflower CV "Embrapacontrasting
confidence: 99%
“…O girassol (Helianthus annuus L.) é uma cultura que se destaca em sistemas de produção de grãos e biodiesel por apresentar diversas vantagens agronômicas como ciclo curto, boa produtividade, elevadas qualidade e rendimento em óleo (MORAIS et al, 2011).…”
Section: Introductionunclassified
“…Apesar dos inconvenientes relacionados ao uso de água com qualidade inferior, algumas estratégias podem ser utilizadas para minimizar os impactos negativos do seu aproveitamento na irrigação, entre elas: escolha de espécies ou cultivares mais tolerantes, utilização dessas fontes de água nos estádios de maior tolerância das culturas, mistura de águas de diferentes qualidades, uso cíclico de fontes de água com diferentes concentrações salinas, além de diversas outras práticas (LACERDA et al, 2009). Pesquisas recentes enfocaram o manejo diferenciado da irrigação com água salina em diversas culturas (BOTÍA et al, 2005;CHAUHAN;SINGH;GUPTA, 2008;HAMDY;SARDO;FARRAG GHANEM, 2005;LACERDA et al, 2009;MALASH;FLOWERS;RAGAB, 2005;MORAIS et al, 2011;MURTAZA;GHAFOOR;QADIR, 2006). Outros estudos foram realizados para avaliar a influência da irrigação com água salina na mamoneira e vários deles indicaram suscetibilidade dessa espécie (CAVALCANTI et al, 2005;PINHEIRO et al, 2008;S I LVA et al, 2005S I LVA et al, e 2008.…”
Section: Introductionunclassified